Investigating the Inactivation Mechanism of Bacillus subtilis Spores by High Pressure CO2 - Rao, Lei; Zhao, Feng; Wang, Yongtao; Chen, Fang; Hu, Xiaosong; Liao, Xiaojun (Frontiers in Microbiology, 2016)
The objective of this study was to investigate the inactivation mechanism of Bacillus subtilis spores by high pressure CO2 (HPCD) processing. The spores of B. subtilis were subjected to heat at 0.1 MPa or HPCD at 6.5-20 MPa, and 64-86ºC for 0-120 min. The germination, the permeability of inner membrane (IM) and cortex, the release of pyridine-2, 6-dicarboxylic acid (DPA), and changes in the morphological and internal structures of spores were investigated. The HPCD-treated spores did not lose heat resistance and their DPA release was lower than the inactivation, suggesting that spores did not germinate during HPCD. The flow cytometry analysis suggested that the permeability of the IM and cortex of HPCD-treated spores was increased. Furthermore, the DPA of the HPCD-treated spores were released in parallel with their inactivation and the fluorescence photomicrographs showed that these treated spores were stained by propidium iodide (PI), ensuring that the permeability of IM of spores was increased by HPCD. The scanning electron microscopy (SEM) photomicrographs showed that spores were crushed into debris or exhibited a hollowness on the surface, and the transmission electron microscopy (TEM) photomicrographs exhibited an enlarged core, ruptured and indistinguishable IM and a loss of core materials in the HPCD-treated spores, indicating that HPCD damaged the structures of the spores. These findings suggested that HPCD inactivated B. subtilis spores by directly damaging the structure of the spores, rather than inducing germination of the spores.